An investigation of the effects of ivermectin on blood serum, semen hyaluronidase activities and spermatological characteristics in sheep - Tanyildizi, S; Bozkurt, T (Tubitak Scientific & Technological Research Council Turkey, 2002)
This study was carried out to investigate the effects of ivermectin on the hyaluronidase activities of blood serum and semen and on the sperm characteristics in sheep. In this investigation 18 sheep, at the age of 2 year's and weighing between 50-60kg were used. After the administration of ivermectin subcutanously at a dose of 0.2 mg/kg, semen and blood samples were taken at different times. The hyaluronidase activities of blood serum and semen samples in sheep were determined to increase significantly (p<0.001) when compared with control groups from the first hour to the 120(th) hour. Furthermore, there was a significant difference (p<0.05) between the hyaluronidase activities of serum and semen in sheep. After the injection of ivermectin subcutanously at a dose of 0.2 mg/kg, the values of sperm concentration were demonstrated to decrease highly significantly (p<0.001) in comparison with the control group. Although the semen volume levels of rams increased significantly (p<0.01) at the first, on the 48(th) and 72(nd) hours, the same levels were observed to decline significantly (p<0.01) when compared with control groups at 24, 96, 120 and 168 hours. In addition, the rates of sperm motility were established to diminish significantly (p<0.01) in comparison with the control group at all times except the first hour. No differences were observed of abnormal spermatozoa rates when compared with the control group. Furthermore, there was no correlation between hyaluronridase activities of serum or semen with sperm characteristics. These findings indicate that ivermectin increases hyaluronidase activity of serum and semen in sheep, but it decreases sperm motility and concentrations. In conclusion, the use of ivermectin is not suitable during ramming season and in rams used for breeding due to the deleterious effects on fertility.
Keywords: ivermectin; hyaluronidase; sheep; sperm